Development of full-length cell-culture infectious clone and subgenomic replicon for a genotype 3a isolate of hepatitis C virus. (24th December 2021) - Chen, Mingxiao; Xu, Yi; Li, Ni; Yin, Ping; Zhou, Qing; Feng, Shengjun; Wu, Tiantian; Wei, Lai; Wang, Haihe; Fu, Yongshui; Li, Yi-Ping
Abstract : Hepatitis C virus (HCV) genotype 3 is widely distributed, and genotype 3-infected patients achieve a lower cure rate in direct-acting antiviral (DAA) therapy and are associated with a higher risk of hepatic steatosis than patients with other genotypes. Thus, the study of the virology and pathogenesis of genotype 3 HCV is increasingly relevant. Here, we developed a full-length infectious clone and a subgenomic replicon for the genotype 3a isolate, CH3a. From an infected serum, we constructed a full-length CH3a clone, however, it was nonviable in Huh7.5.1 cells. Next, we systematically adapted several intergenotypic recombinants containing Core-NS2 and 5′UTR-NS5A from CH3a, and other sequences from a replication-competent genotype 2 a clone JFH1. Adaptive mutations were identified, of which several combinations facilitated the replication of CH3a-JFH1 recombinants; however, they failed to adapt to the full-length CH3a and the recombinants containing CH3a NS5B. Thus, we attempted to separately adapt CH3a NS5B-3′UTR by constructing an intragenotypic recombinant using 5′UTR-NS5A from an infectious genotype 3a clone, DBN3acc, from which L3004P/M in NS5B and a deletion of 11 nucleotides (Δ11nt) downstream of the polyU/UC tract of the 3′UTR were identified and demonstrated to efficiently improve virus production. Finally, we combined functional 5′UTR-NS5A and NS5B-3′UTR sequences that carried the selected mutations to generate full-length CH3a with 26 or 27 substitutions (CH3acc), and both revealed efficient replication and virus spread in transfected and infected cells, releasing HCV of 10 4.2 f.f.u. ml −1 . CH3acc was inhibited by DAAs targeting NS3/4A, NS5A and NS5B in a dose-dependent manner. The selected mutations permitted the development of subgenomic replicon CH3a-SGRep, by which L3004P, L3004M and Δ11nt were proven, together with a single-cycle virus production assay, to facilitate virus assembly, release, and RNA replication. CH3acc clones and CH3a-SGRep replicon provide new tools for the study of HCV genotype 3.